1998
DOI: 10.1021/jp9824656
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Aromatic-Functionalized Amphiphiles:  The Role and Consequences of Aromatic−Aromatic Noncovalent Interactions in Building Supramolecular Aggregates and Novel Assemblies

Abstract: This feature article presents an overview of a study of several different aromatic-functionalized amphiphiless fatty acid and phospholipid derivatives. These amphiphiles form organized assemblies when the fatty acids are spread as monolayers at the air-water interface or when the phospholipids are dispersed in aqueous solutions. For a wide range of aromatic chromophoresstrans-stilbene derivatives and a series of "vinylogues" (1,4-diphenyl-1,3-butadiene and 1,6-diphenyl-1,3,5-hexatriene), diphenylacetylenes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 88 publications
10
86
0
1
Order By: Relevance
“…These interactions have multiple points of intermolecular contact with variable geometries and may contain a vast range of different functional groups (Hunter et al, 2001). Moreover, these interactions play a crucial part in biomolecules and pure organics selfassembly (Azriel and Gazit, 2001;Hunter et al, 2001;Whitten et al, 1998). Harmata and Barnes (1993) who also studied the packing and density of a complex organic substance concluded that the high densities observed indicate the efficiency of the packing, which are dominated by edge-to-face stacking of aromatic moieties.…”
Section: The Effective Density Of Srfa Bulk and Fractionsmentioning
confidence: 99%
“…These interactions have multiple points of intermolecular contact with variable geometries and may contain a vast range of different functional groups (Hunter et al, 2001). Moreover, these interactions play a crucial part in biomolecules and pure organics selfassembly (Azriel and Gazit, 2001;Hunter et al, 2001;Whitten et al, 1998). Harmata and Barnes (1993) who also studied the packing and density of a complex organic substance concluded that the high densities observed indicate the efficiency of the packing, which are dominated by edge-to-face stacking of aromatic moieties.…”
Section: The Effective Density Of Srfa Bulk and Fractionsmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] Azobenzenes of donor-acceptor type have been found to form characteristic aggregates depending on the solvent composition, polarity, and the solute concentration. Studies directed towards aggregation of azobenzenes have mainly concentrated on: 1) simpler azobenzene molecular entities of donor-acceptor and electronically symmetric type; [39,40] 2) surfactant-like azobenzene derivatives functionalized with long alkyl chains and apexed with a polar head group; [41,42] and 3) azo moieties with polar or nonpolar head groups, appended as side chains on polymeric backbones. [43,44] With the aim of developing photomodulated phthalocyanine J-aggregates, a-aryl/ alkoxy-substituted zinc phthalocyanine dyads (3-azo-ZnPc and 4-azo-ZnPc) have been synthesized by LiHong Niu et al [45] In noncoordinating solvents, the 3-azo-ZnPc could be effectively photocontrolled as a result of changes in the geometry and dipole moment of azobenzene on the dyad framework.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other proposals, the proto-genes directly interact with the lipid; this requires a less sophisticated spatial organisation than vesicles (see e.g. (Apel et al, 2002)), making micelles (Whitten et al, 1998) or even less organized lipid aggregates plausible. A scheme of the replication mechanism is shown in Fig.…”
Section: Molecular Replicatorsmentioning
confidence: 83%